Knowledge Management Model for Community Based Tourism of Satun Community Based Tourism Network, Thailand - Tungseng, Taweesin; Madhyamapurush, Warach; Sreesoompong, Phatpitta (Mekong-Salween Civilization Studies Journal, 2016)
The purpose of the research entitled “Knowledge Management Model for Community Based Tourism of Satun Community Based Tourism Network, Thailand” was to learn the necessary information of Satun Community Based Tourism Network. This research was a qualitative study which used “knowledge management” for collecting data starting from determining the goal for managing knowledge and learning exchange with the expert operators, including storing the knowledge of Satun Community Based Tourism Network by using information technology as a tool. From the result study on the context of the necessary information of Satun Community Based Tourism Network by using knowledge management as a tool and emphasizing on learning exchange in order to collect data of Satun Community Based Tourism Network, it was found that the Group’s operation according to the level of knowledge and understanding of the Community Based Tourism were categorized into three groups: 1) a group of people who have good knowledge, 2) a group of people who have moderate knowledge 3) a group of people who have little or no knowledge. To collect information from the community as to develop information systems for Community Based Tourism Network of Satun, there were five main points needed information; 1) information on basis of community 2) information on resources and cultural heritage, 3) information on community organizations 4) information on management and 5) information on learning management. All of these used appropriate knowledge management as a tool. It proceeded with 4 main steps as follows; 1) Knowledge Shape/work 2) Knowledge Store 3) Knowledge Share 4) Knowledge Sustainable The researcher would like to suggest that Satun Community Based Tourism Network should have the ongoing knowledge management activities, both formal and informal to construct the relationships and learning exchange all the time.